A treatise on three-dimensional vibrations of a class of elastic solids - Hung, Kin Chew. (2009)
This work presents a comprehensive study on the three-dimensional vibrations of a class of elastic solids in the forms of beams, plates and shells. A global method developed on the three-dimensional linear elasticity theory in conjunction with the Ritz minimum energy principle is used in the analyses.